Comparison of Micronutrient Intervention Strategies in Ghana and Benin to Cover Micronutrient Needs: Simulation of Bene-Fits and Risks in Women of Reproductive Age - Dass, Mamta (Nutrients, 2021)
Overlapping micronutrient interventions might increase the risk of excessive micronutrient intake, with potentially adverse health effects. To evaluate how strategies currently implemented in Benin and Ghana contribute to micronutrient intake in women of reproductive age (WRA), and to assess the risk for excess intakes, scenarios of basic rural and urban diets were built, and different on-going interventions were added. We estimated micronutrient intakes for all different scenarios. Four types of intervention were included in the scenarios: fortification, biofortification, supplementation and use of locally available nutrient-rich foods. Basic diets contributed poorly to daily micronutrient intake in WRA. Fortification of oil and salt were essential to reach daily requirements for vitamin A and iodine, while fortified flour contributed less. Biofortified products could make an important contribution to the coverage of vitamin A needs, while they were not sufficient to cover the needs of WRA. Iron and folic acid supplementation was a major contributor in the intake of iron and folate, but only in pregnant and lactating women. Risk of excess were found for three micronutrients (vitamin A, folic acid and niacin) in specific contexts, with excess only coming from voluntary fortified food, supplementation and the simultaneous overlap of several interventions. Better regulation and control of fortification and targeting of supplementation could avoid excess intakes.